Social Identity and Organisational Citizenship Behaviour: Key Predictors of Critical Care Nursing Practice - Islam Oweidat; Asma Ziadeh; Mutaz I. Othman; Amal Al‐Tarawneh; Khalid Al‐Mugheed; Nadiah A. Baghdadi; Sally Mohammed Farghaly Abdelaliem (Nursing in Critical Care, 2026)
ABSTRACT Background Organisational Citizenship Behaviour (OCB) and Social Group Membership (SGM) are critical for enhancing organisational effectiveness and nurse well‐being. While SGM's role in fostering OCB is acknowledged globally, its bidirectional relationship remains underexplored in nursing contexts. Aim To identify predictors of SGM and OCB among critical care nurses and examine their reciprocal relationship. Study Design A cross sectional, correlational study was conducted. Validated tools, the Multiple Group Membership (MGM) Scale and Organizational Citizenship Behavior Scale (OCBS) were used. Data were analysed via Pearson correlation and multiple linear regression. Results Among 163 critical care nurses were included, significantly predicted OCB ( β = 0.643, p < 0.001), explaining 78.2% of its variance. Work‐related factors, including nursing experience ( β = 0.503), weekly workload ( β = 0.350) and night shifts ( β = 0.482), also predicted OCB. Conversely, OCB predicted SGM ( β = 0.643, p < 0.001), with 47.2% variance explained. Age, experience and night shifts further influenced SGM. A bidirectional relationship between SGM and OCB was confirmed, moderated by organisational demands and support structures. Conclusions Enhancing nurses' engagement in professional and social networks fosters a reinforcing cycle of prosocial behaviour and social connectivity. Hospital administrators should prioritise SGM‐promoting strategies, such as mentorship and professional associations, to improve OCB, job satisfaction and patient care outcomes. Relevance to Clinical Practice This study is relevant to critical care practice as it highlights how social identity and OCB influence teamwork, collaboration and voluntary supportive actions among nurses. Strong professional identification enhances cooperation, reduces conflict and improves communication, leading to better coordination, efficiency and ultimately higher quality patient care in critical settings.